Evaluation of the functionality, safety, and environmental impact of the new pop-up bicycle lane on Konstantinos Karamanlis Avenue in Thessaloniki, Greece. Issue 1 (1st December 2022) - Kinis, Dionysios; Palantzas, Georgios; Nalmpantis, Dimitrios
Abstract: The COVID-19 pandemic had some positive results regarding the established policy of the European Union (EU) of promoting active mobility, such as the creation of temporary bicycle lanes and paths, to facilitate mobility in the era of social distancing. Such a bicycle lane was constructed in the city of Thessaloniki, Greece, on Konstantinos Karamanlis Avenue. In the summer of 2020, during the COVID-19 pandemic, a bicycle lane was constructed on Konstantinos Karamanlis Avenue. In the present paper, a questionnaire survey is presented regarding the functionality, effectiveness, safety, and environmental impact of this specific bicycle lane. In total, 228 people participated in the survey. They were able to evaluate the different problems encountered on the bicycle lane and the behavior of the other road users and to make judgments and suggestions for its improvement. Important conclusions emerge from the collected data, such as that the citizens believe that there are significant problems with the safety of the bicycle lane and less important problems with its operation. Finally, it seems that there is a great desire to strengthen active mobility and especially cycling in the city of Thessaloniki, given that the infrastructure will provide the appropriate safety.